Two-load method for distinguishing between muscle force, velocity, and power-producing capacities - Jaric, S. (Sports Medicine, 2016)
It is generally accepted that muscles may have different mechanical capacities, such as those for producing high force (F), velocity (V), and power (P) outputs. Nevertheless, standard procedures for evaluation of muscle function both in research and in routine testing are typically conducted under a single mechanical condition, such as a single external load. Therefore, the observed outcomes do not allow for distinguishing between the different muscle capacities. As a result, the outcomes of most routine testing procedures are of limited informational value, whereas a number of issues debated in research have originated from arbitrarily interpreted experimental findings regarding specific muscle capacities. A solution for this problem could be based on the approximately linear and exceptionally strong F-V relationship typically observed from various functional tasks performed under different external loads. These findings allow for the `two-load method` proposed here: the functional movement tasks (e.g., maximum jumping, cycling, running, pushing, lifting, or throwing) should be tested against just two distinctive external loads. That is, the F-V relationship determined by two pairs of the F and V data could provide the parameters depicting the maximum F (i.e., the F-intercept), V (V-intercept), and P (calculated from the product of F and V) output of the tested muscles. Therefore, the proposed two-load method applied in both research and routine testing could provide a deeper insight into the mechanical properties and function of the tested muscles and resolve a number of issues debated in the literature.